Identifying support needs and intervention opportunities for perinatal fathers: an exploratory sequential mixed methods study - Rayburn, Stephanie, author; MacPhee, David, advisor; Braungart-Rieker, Julie, advisor; Lucas-Thompson, Rachel, committee member; Prince, Mark, committee member (Colorado State University. Libraries, 2023)
The transition to fatherhood is a time of increased stress and risk for depressive and anxiety disorders for fathers. Father adjustment affects family well-being, but support programs that target perinatal fathers are not widely available, and it can be difficult to engage fathers in the programs that are available. Identifying the support needs of perinatal fathers and opportunities for intervention is an important and underexplored avenue for promoting early healthy family development. The following dissertation includes a review of developmental theories and extant literature and proposes a model of paternal perinatal development. Three studies are then presented using an exploratory mixed methods design. Study A explores perinatal father experiences and perceptions of their support needs. Study B quantitatively assesses social support as a predictor of parenting engagement, role conflict, and well-being in postpartum fathers. Study C investigates qualitative and quantitative evidence for a proof-of-concept evaluation of a piloted community-based group intervention program called DadSpace. Findings from Study A indicate that fathers find value in connecting with other fathers and are interested in support and information that are relevant to fathers. Findings from Study B indicate that both social support and self-efficacy are significant predictors of postpartum father parenting engagement and well-being, including work-home role conflict and satisfaction, parenting stress, depression, and anxiety. Findings from Study C demonstrate that perinatal fathers find value in a program that connects them with other fathers and supports them in exploring issues relevant to them; however, recruitment remains a challenge.
Keywords: fatherhood; parenting; postpartum; fathers; development; perinatal